Fluctuations Mitigation of Variable Speed Wind Turbine through Optimized Centralized Controller - Ali Mohammadi; Sajjad Farajianpour; Saeed Tavakoli; S. Masoud Barakati (Institute of Advanced Engineering and Science, 2012)
A wind energy conversion system (WECS) including a variable wind turbine in grid-connected mode is considered to control. In this paper, each component of WECS model is systematically presented and then the integrated overall model is validated.Regarding to nonlinear nature of WECS and the complex system structure as multiple-input- multiple-output (MIMO),control procedure counters the problem which strategy to handle.To simplify the control policy, a centralized controller which is compatible with systematic modelling introduced, is employed. In other hand to augment the centralized controller performance, an optimization based on genetic algorithm (GA) is accomplished. Simulation results demonstate the proper efficiency in fluctuations mitigation. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.854